Analisis Tingkat Kepuasan Santriwati dalam Menabung di BMT Ar-Raudhlatul Hasanah Medan Demi Menggapai Kemandirian - Nudia Yultisya; Aqwa Naser Daulay (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to identify the level of satisfaction of customers/female students who save money at Baitul Maal Wat Tamwil (BMT) Raudhah with regard to the saving services provided by this cooperative. The research method used in this study is Quantitative Descriptive with data collection techniques through a survey, where data is gathered through the distribution of questionnaires to customers/female students of BMT Raudhah. The results of this survey are then analyzed statistically to determine the level of customer satisfaction with the aspects of saving services provided by BMT Raudhah. The results of this research indicate that the majority of customers/female students of BMT Raudhah have a very high level of satisfaction with the saving services provided by BMT Raudhah.